2011
DOI: 10.1007/s00468-011-0624-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of leaf vein density and climate relationship of Quercus variabilis populations remains unchanged with environmental changes

Abstract: The leaf vein traits of plants result partially from adaptations to environmental factors during the longterm evolution. However, no general conclusion on the variation trend of the vein density along a climate gradient or the response of such vein density-climate relationship pattern to climate changes has been made. We examined the variations in leaf vein density and other leaf traits of oriental oak (Quercus variabilis) in 10 in situ populations (in situ populations) across temperate-subtropical biomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…3). The results of PL were different from Fallah et al (2012), but these results confirm the results of Sack et al (2003), Yousefzadeh et al (2009), Ghorbanli et al (2009) and Zhu et al (2012). It seems that each plant has its own plasticity-related strategy because there have been presented different reports for different species.…”
Section: Distance From Road Sidesupporting
confidence: 59%
See 1 more Smart Citation
“…3). The results of PL were different from Fallah et al (2012), but these results confirm the results of Sack et al (2003), Yousefzadeh et al (2009), Ghorbanli et al (2009) and Zhu et al (2012). It seems that each plant has its own plasticity-related strategy because there have been presented different reports for different species.…”
Section: Distance From Road Sidesupporting
confidence: 59%
“…In general, the number of veins (V) and stomatal dimensions (SL, SW) has minimal plasticity, and stomatal density and leaf dimensions have the highest variability (Zhu et al, 2012). Zhu et al (2012) found that the vein density was less sensitive to environmental changes, and these authors also report that the vein trait was a protected trait. In general, different environments, and consequently different microclimates can affect the variability in leaf quantitative traits.…”
Section: Distance From Road Sidementioning
confidence: 99%
“…The plasticity of stomatal density depends on more environmental factors, such as: air humidity (Torre et al 2003), vapor pressure deficit (Leuschner 2002), temperature (Beerling and Chaloner 1993;Zhu et al 2012), etc. For instance, Lichtenthaler et al (1981) reported that sun leaves of beech possessed significantly higher stomatal density than shade leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Vein traits are thought to reflect the gas and water exchange conditions at the interface between the leaves and the atmosphere, which are greatly influenced by the climatic factors affecting the leaf [11,12]. Studies focusing on interspecific patterns between plant traits and climatic factors have identified a correlation between leaf vein density and mean annual precipitation (MAP), and dryness of soil water availability can lead to higher leaf venation densities [13]. Phenotypic plasticity is one of two complementary ecological strategies and it refers to the ability of a specific genotype to shape various phenotypes in response to environmental variation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Venation properties have been recognized as a type of phenotypic plasticity that is caused by ontogeny. There have been numerous reports on the correlations between leaf vein density and leaf area [15], epidermal cell size [16], stomatal density [17][18][19], stomatal conductance [19], hydraulic conductance [19,20], and photosynthesis [13]. However, variations in leaf venation and leaf vein density under different environmental conditions have not been widely reported until recently [21], especially for endangered species.…”
Section: Introductionmentioning
confidence: 99%